Issues of Theory and Practice of Development of Electronic Democracyin the Field of Nature Protection in Russia - A. P. Anisimov (Сибирское юридическое обозрение, 2019)
The article analyzes the theory and practice of e-democracy in the field of environmental protection in Russia, shows the potential for the introduction of environmental petitions and environmental voting, analyzes the practice of interaction between citizens and authorities on the websites of federal and regional environmental authorities of Russia. As a result of the study, the conclusion is substantiated that today in the activities of environmental authorities we observe only the first steps to create a system of electronic democracy, which include the possibility of obtaining information on the website of the authorities, as well as “unilateral interaction”, that is, the ability of citizens and legal entities to download from the website the forms of certain documents. At the moment, additional efforts are needed by the authorities to switch to bilateral electronic interaction, which will be an important step towards the personal involvement of all interested citizens in the process of making environmental management decisions.